Hakikat Pembiayaan Pendidikan - Armida, Armida (Media Akademika, 2007)
This article is trying to open broad vision on educational budgeting or financial management. This descriptive analytical approach article highlights the vision of some experts on education budget/finance starting from the nature of education economic finance or budget-discussing direct cost and indirect one. Then, the writer highlights the revenues or incomes and the real implementation of the budget in schools as well as its affectivity and efficiency. This article is ended with the closing remarks.